High-light stress and photoprotection in Umbilicaria antarctica monitored by chlorophyll fluorescence imaging and changes in zeaxanthin and glutathione - Barták, M; Hájek, J; Vráblíková, H; Dubová, J (Plant biology (Stuttgart, Germany), 2004)
The effect of high light on spatial distribution of chlorophyll (Chl) fluorescence parameters over a lichen thallus (Umbilicaria antarctica) was investigated by imaging of Chl fluorescence parameters before and after exposure to high light (1500 micro mol m (-2) s (-1), 30 min at 5 degrees C). False colour images of F (V)/F (M) and Phi (II) distribution, taken over thallus with 0.1 mm (2) resolution, showed that maximum F (V)/F (M) and Phi (II) values were located close to the thallus centre. Minimum values were typical for thallus margins. After exposure to high light, a differential response of F (V)/F (M) and Phi (II) was found. The marginal thallus part exhibited a loss of photosynthetic activity, manifested as a lack of Chl fluorescence signal, and close-to-centre parts showed a different extent of F (V)/F (M) and Phi (II) decrease. Subsequent recovery in the dark led to a gradual return of F (V)/F (M) and Phi (II) to their initial values. Fast (30 min) and slow (1 - 22 h) phase of recovery were distinguished, suggesting a sufficient capacity of photoprotective mechanisms in U. antarctica to cope with low-temperature photoinhibition. Glutathione and xanthophyll cycle pigments were analyzed by HPLC. High light led to an increase in oxidized glutathione (GSSG), and a conversion of violaxanthin to zeaxanthin, expressed as their de-epoxidation state (DEPS). The responses of GSSG and DEPS were reversible during subsequent recovery in the dark. GSSG and DEPS were highly correlated to non-photochemical quenching (NPQ), indicating involvement of these antioxidants in the resistance of U. antarctica to high-light stress. Heterogeneity of Chl fluorescence parameters over the thallus and differential response to high light are discussed in relation to thallus anatomy and intrathalline distribution of the symbiotic alga Trebouxia sp.
Keywords: Acclimatization; glutathion; fotosyntetická reakční centra (proteinové komplexy); Glutathione; beta Carotene; Symbiosis; zeaxanthiny; aklimatizace; Fluorometry; Cold Temperature; lišejníky; chlorofyl; Zeaxanthins; Light; Lichens; xanthofyly; fluorometrie; Photosynthetic Reaction Center Complex Proteins; Xanthophylls; symbióza; světlo; nízká teplota; mikroskopie; Chlorophyll; beta-karoten; Microscopy; Eukaryota